Dvostopenjska vetrna turbina - Schweiger, Vlado (Strojniški vestnik, 2005)
In this paper we present an approach to increasing the wind-energy efficiency of a turbine by using a double-stage counter-rotating wind-turbine installation. The theoretical, aerodynamic efficiency, known as the Betz limit, is increased from 0.593 up to 0.640. A numerical analysis was made to establish the power and kinematic characteristics of single- and double-stage models. The results of the analysis show a significant increase in the aerodynamic efficiency with a second-stage installation. These results point toward the need for a further investigation of the double-stage model.
Keywords: turbine vetrne; turbine dvostopenjske; izkoristek aerodinamični; analize numerične; vetrne turbine; matematični modeli; aerodinamika